THE ATTITUDES OF INTERNATIONAL STUDENTS IN INDIA TOWARDS ENGLISH - Wildan Mahir Muttaqin (UIN Raden Mas Said Surakarta, 2016)
English is now considered as global language, and with every single day its users are increasing numerously. The paper aims to investigate the international students’ attitudes towards English language focusing on a case of International students’ in India. As the central university, The English and Foreign Lnguages (EFL) University India has many international students from a wide range of countries. The attitudes are in language skills and in other perspectives. Upon the completion of the collection of data, these were analyzed, computed and tabulated using MS Excel.The study incorporates quantitative approach and has used close ended questionnaire to collect data from the participants. A total number of twenty students participated in the study. From the findings of the data, The research shows that they had shown a positive attitude towards use of English or an increase in the use of English. They believed that learning needs process. Motivation and self-confidence are also main factors to master English comprehensively. They also believe that EFL University is the best place in India to study English intensively.